2017
DOI: 10.1088/1367-2630/aa8ed9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the target aspect ratio and intrinsic reactivity onto diffusive search in bounded domains

Abstract: We study the mean first passage time (MFPT) to a reaction event on a specific site in a cylindrical geometry-characteristic, for instance, for bacterial cells, with a concentric inner cylinder representing the nuclear region of the bacterial cell. A similar problem emerges in the description of a diffusive search by a transcription factor protein for a specific binding region on a single strand of DNA. We develop a unified theoretical approach to study the underlying boundary value problem which is based on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 52 publications
4
59
0
Order By: Relevance
“…which corresponds to the surface-averaged MFPT investigated in Ref. [38]. This result is expected for diffusion in a bounded domain.…”
Section: B the Right-tail Of The Fpt Distributionsupporting
confidence: 71%
See 2 more Smart Citations
“…which corresponds to the surface-averaged MFPT investigated in Ref. [38]. This result is expected for diffusion in a bounded domain.…”
Section: B the Right-tail Of The Fpt Distributionsupporting
confidence: 71%
“…We note that the effect of κ on the shape of the full distribution of the FPT is a novel feature here. The only available previous analysis concerned solely its effect on the MFPT, and showed that in related settings it can indeed be decisive [28,38]. This naturally raises the question of the effects of a finite reactivity beyond the MFPT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) The concept of the search-controlled versus barrier-controlled NEP proposed in [4,30] holds indeed for the mean FRT, see equation (C.6). In contrast, we observe that two other important characteristic time-scales-t mp and t c -are unaffected by the reactivity and solely depend on the diffusion coefficient and the geometry.…”
mentioning
confidence: 93%
“…On the other hand, homogenization techniques were used to substitute piecewise constant reactivity κ(s) by an effective homogeneous reactivity [31][32][33][51][52][53][54][55][56][57][58]. More recent works investigated how the mean reaction time is affected by a finite lifetime of diffusing particles [59][60][61], by partial reactivity and interactions [63,64], by target aspect ratio [65], by reversible target-binding kinetics [66,67] and surface-mediated diffusion [68][69][70][71], by heterogeneous diffusivity [72], and by rapid re-arrangments of the medium [73][74][75]. Some of the related effects onto the whole distribution of reaction times were analyzed [76][77][78][79][80].…”
Section: Introductionmentioning
confidence: 99%